2001
DOI: 10.1034/j.1398-9995.2001.056008771.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of horse allergen in the ambient air, detected with sandwich ELISA

Abstract: We have developed a sensitive, horse-allergen-specific, mAb assay allowing detection of low levels of horse allergens. Raised levels of horse allergen were found outdoors only in the close vicinity of the stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…In Sweden, the official recommendation since 1989 is 500m (National board of housing, building and planning 1998), but not much was known about dispersion of horse allergen in ambient air at that time and no assays were available for detection of horse allergen. Later studies have shown that horse allergens do not disperse more than about 50-100m from source, which is from stables and fields where horses are kept (Emenius et al, 2001;Elfman et al, 2008). On days with increased wind speed and with prevailing winds, horse allergen levels can sometimes be detected up to 200-450m from the source.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, the official recommendation since 1989 is 500m (National board of housing, building and planning 1998), but not much was known about dispersion of horse allergen in ambient air at that time and no assays were available for detection of horse allergen. Later studies have shown that horse allergens do not disperse more than about 50-100m from source, which is from stables and fields where horses are kept (Emenius et al, 2001;Elfman et al, 2008). On days with increased wind speed and with prevailing winds, horse allergen levels can sometimes be detected up to 200-450m from the source.…”
Section: Discussionmentioning
confidence: 99%
“…The extract was aliquoted and stored as a 1/5 dilution with thimerosal at 4–8°C. To compare levels of horse allergen (Allergon) with an earlier study [7] the standard was set to a horse standard from NIBSC (National Institute for Biological Standards and Control, UK). Protein in both standards were determined with the Micro BCA protein assay reagent kit (Pierce Chemical Company, USA) using BSA as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was basically performed according to the protocol published by Emenius et al [7] (reagents were generously supplied by Mabtech, Stockholm, Sweden), except for the different horse allergen standard used in this study. The standard curve range was 2–64 U/ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations